Enhancing Student Competence Through Visits to Karangmumus River School to Study Its Ecology Using the River Continuum Concept - Mulyanto, Ahmad Shiddiq; Kaunang, Merinda Margaret; Fauziah, Fenty; Fitriansyah; Yamin, Bun; Rahmadi, Muhammad Harry (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This study aims to enhance student's environmental awareness, particularly regarding river ecology, through an experiential learning approach. The primary activity in this research is a field visit by students to the Karangmumus River School, allowing them to compare theoretical knowledge learned in class with real-world conditions. Method: The study employs a qualitative method with a descriptive approach. Data was collected through observations, interviews, and student reflections after the field visit. Practical Application: The findings reveal that the visit significantly improved students' understanding of river conservation and the impact of human activities on river ecosystems. Furthermore, the activity motivated students to contribute to environmental preservation efforts. Thus, integrating classroom theory with field experiences effectively fostered environmental awareness among students. Conclusion: This study shows that experiential learning through field visits to the Karangmumus River School significantly increases students' awareness of river ecology and environmental conservation.